2004
DOI: 10.1111/j.1464-410x.2004.05019.x
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng improves survival and sperm quality in guinea pigs exposed to 2,3,7,8‐tetrachlorodibenzo‐ p‐dioxin

Abstract: administered to the P and G groups for 12 weeks from 1 week before TCDD exposure, and to the C groups for 10 weeks from 1 week after TCDD exposure. After a 4-week discontinuation of PG-WE treatment after the 13th week the surviving males were then tested for fertility by mating them with females. The litter size, death rate, male/ female birth ratio and physical abnormalities of the progeny were investigated. After confirming delivery of the offspring, the parent males were killed at 40 weeks, their testes wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…We also demonstrated that KRG improved liver and kidney function, sperm motility, testosterone levels, and spermatogenesis in old rats. From these results, together with our previous reports [19][20][21], we conclude that KRG effectively overcomes the testicular dysfunction of aging. These physiochemical results lead us to propose additional biochemical studies and further development of ginseng for sexual dysfunction, especially to promote spermatogenesis in men.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also demonstrated that KRG improved liver and kidney function, sperm motility, testosterone levels, and spermatogenesis in old rats. From these results, together with our previous reports [19][20][21], we conclude that KRG effectively overcomes the testicular dysfunction of aging. These physiochemical results lead us to propose additional biochemical studies and further development of ginseng for sexual dysfunction, especially to promote spermatogenesis in men.…”
Section: Discussionmentioning
confidence: 56%
“…Studies have shown that KRG helps prevent diabetes mellitus [13], atherosclerosis [14], erectile dysfunction [15], immune dysfunction [16], carcinogenesis [17], and physicochemical stress [18] among other disorders. Additionally, we reported that the administration of KRG water extract (KRG-WE) protects testicular function [19], and improves sperm survival rate and quality in guinea pigs exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin [20]. KRG is used for many reasons, including its reasonable price, ready availability, and safety.…”
Section: Introductionmentioning
confidence: 99%
“…. 인삼의 약리작용은 다양하게 연구되었으며, 그중 생식기능 과 관련된 작용으로 인삼은 부신피질, 성선에 대한 흥분작용 이 있어서 guinea pig 암컷의 성기능 성숙을 촉진시켜서 자 궁과 난소의 중량을 증가시키고, 수컷에서는 정자 수를 증가 시키고 활동력을 증강시키며 고환과 부고환의 중량을 증가시 키며 27) , 인삼 사포닌 중 ginsenoside Rb2와 Rc는 사람에서 남성 정자의 질 개선에 효과가 있음이 알려져 있다 26) . 인삼은 원인불명의 정자결핍증 환자군과 특발성 정맥류를 가진 정자 결핍증 환자군 모두에서 정자 수 및 정자운동성의 현저한 증 가를 보였으며, 정상인에 대해서도 유의한 증가를 보였다 28) .…”
Section: 인삼이 Catsper4 단백질 발현에 미치는 영향unclassified
“…Geusau et al (1999) showed that Olestra reduces the elimination halflife of TCDD from c. 7 to 1-2 a in highly exposed persons. Also ginseng ingredients (Moon et al 2005), medicinal carbon (Kamimura et al 1988) and chlorophyllin-chitosan (Kitamura 2005) have increased excretion of PCDD/Fs in humans and other mammals exposed to high levels; ginseng  Management options and technological measures 7 also has other protective effects (e.g., Hwang et al 2004). However, psychological resistance to detoxifying treatment may be a key obstacle (Schnare et al 1982).…”
Section: Therapies Of Adverse Effectsmentioning
confidence: 99%